Identifying Mainstreaming Climate Change Adaptation Efforts for Children into the West Java Development Planning - Novi Puspitasari; Djoko Santoso Abi Suroso; Saut Aritua Hasiholan Sagala (The Indonesian Journal of Planning and Development, 2017)
West Java is an Indonesian Province which has a high risk of climate change impacts particularly in terms of increased exposure from many natural disasters. A natural disaster occurs frequently in the West Java Province, making the region vulnerable due to the biggest population in Indonesia it belongs to. Children are the most vulnerable population facing climate change impact because their physiological condition is not fully developed yet. They have a low adaptation ability towards the predicted changes. Therefore, mainstreaming climate change adaptation for children into development planning is important. It is also critical in order to induce more effective adaptation program. This paper analyzes how far the current development plan in the West Java Province reckons child adaptation mainstreaming to climate change. Data collection methods used in this research are the secondary method through the related development plan and the primary method through an in-depth interview to the related government institutions. Based on the analysis results using a content analysis, the region has a potential entry point to mainstream the adaptation of climate change into the development plan, involving seven government institutions. The opportunity of entry point from the West Java development plan is found in Badan Pengelolaan Lingkungan Hidup Daerah/BPLHD (the Regional Environmental Management Agency) work plan. However, among these institutions, it is only BPLHD and the Health Department which almost fulfill all of the institutional capacity components to mainstreaming the adaptation of climate change for children into the West Java development planning. Therefore, both institutions are potentially recommended acting for initiators to induce coordination between the seven government institutions to mainstream the adaptation of climate change for children into the West Java development planning.